PESAN BELA NEGARA DALAM WUJUD SILA KETIGA PERSATUAN DAN KESATUAN (STUDI KASUS SPANDUK SIMPATISAN HABIB RIZIEQ SHIHAB) - Enny Nurcahyawati; Zulkarnain Alfisyahrin; Syahid Syahid; Bilqis Kusuma Wardhani (Interpretasi: Communication & Public Relations, 2021)
Defending the state is a patriotic form, both from attitude and behavior, as a form of love for the motherland based on Pancasila and the 1945 Constitution, as well as Bhinneka Tunggal Ika. The application of state defense, among others, can be applied through outdoor media, such as messages inside banners. This study discusses the third principle of unity and integrity that the actions of Habib Rizieq Shihab's sympathizers want to echo through the media of banners. The purpose of this study is to examine three related elements in the concept of state defense, namely, people, regions, and government. This research uses a qualitative method with a communication approach, especially in the encoding process. The results showed that the message of defending the country under the banner of sympathizer Habib Rizieq Shihab was able to represent the value of unity of the third precept of Pancasila. This research is expected to be an academic reference in conveying the message of defending the country in communicative and informative outdoor media.